THE INFLUENCE OF CAREER MANAGEMENT AND ORGANIZATIONAL COMMITMENT ON WORK EFFECTIVENESS WITH COMPETENCY AS A MODERATING VARIABLE OF EMPLOYEES AT PT PLN (PERSERO) UP3 PADANGSIDIMPUAN - Wiwin Sapta Prabudi; Kiki Farida Ferine (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This research investigates the influence of career management and organizational commitment on work effectiveness, with competency acting as a moderating variable among employees at PT PLN (Persero) UP3 Padangsidimpuan. Utilizing a quantitative approach with descriptive and causal methods, the study examines the relationships between these factors. Data was collected via questionnaires from all 86 employees of PT PLN (Persero) UP3 Padangsidimpuan between June and August 2025 and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings offer insights into how strategic career management, organizational commitment, and employee competency can be synergistically designed to foster a conducive, adaptive, and results-oriented work environment, ultimately enhancing work effectiveness within the organization.